Sams teach yourself Visual C♯ 2008 in 24 hours : complete starter kit - Foxall, James D. (Sams teach yourself., 2008)
Sams Teach Yourself Visual C#® 2008 in 24 Hours James Foxall Starter Kit DVD includes Visual C#® 2008 Express Edition In just 24 sessions of one hour or less, you will be up and running with Visual C# 2008. Using a straightforward, step-by-step approach, each lesson builds upon the previous one, allowing you to learn the essentials of Visual C# from the ground up. By the Way notes present interesting pieces of information. Did You Know? tips offer advice or teach an easier way to do something. Watch Out! cautions advise you about potential problems and help you steer clear of disaster. Learn how to ... Use the powerful design environment of Visual Studio 2008 Design a feature-rich interface using components such as tree views and tabs Create robust applications using modern error handling Draw fast graphics using GDI+ Build a database application using ADO.NET Distribute a Visual C# 2008 application James Foxall is vice president of Tigerpaw Software, Inc. (www.tigerpawsoftware.com), a Bellevue, Nebraska, Microsoft Certified Partner specializing in commercial database applications. He manages the development, support, training, and education of Tigerpaw CRM+, an award-winning application that automates contact management, marketing, service and repair, proposal generation, inventory control, and purchasing. Tigerpaw has more than 20,000 licensed users in 27 countries. Foxall's experience in creating certified Office-compatible software has made him an authority on application interface and behavior standards. In addition to being a well-known author, James is an international speaker on Microsoft technologies, has taught at the college level, and contributes to several journals. DVD Includes: Microsoft® Visual C#® 2008 Express Edition On the Web: Register your book at informit.com/title/9780672329906 for access to author code, examples, updates and corrections as they become available. Category: Microsoft Programming Covers: Visual C# 2008 User Level: Beginning.